Indigenous management and sustainability of forest gardens in peninsular Malaysia: implications for conservation - Ismail, Izzaty Khaleda (2024)
Forest gardens in Malaysia have been practiced by the indigenous communities for generations. However, limited study has been conducted on forest gardens in Malaysia especially on the indigenous management and its sustainability. This study examined the indigenous management and sustainability of forest garden in peninsular Malaysia specifically in Selangor. Data were collected from seven indigenous villages practising forest gardens using 86 household surveys, seven focus group discussions, and four key informants’ interviews. Indigenous management was explored following story telling approach while sustainability was assessed by using the five major criteria of Globally Important Agricultural Heritage Systems (GIAHS). Results show that the main activities conducted on the forest gardens were maintenance (87% of the participants) whereby 64% of the participants did not utilise chemical fertilizers or pesticides. It was also found that 62% of the participants that maintain the forest gardens were found to be men. Moreover, 72% of the participants independently maintain the forest gardens as they did not receive any support from government or NGO for the forest gardens. Fruit harvests were found to be used for sale (66%) whereby Durian was the popular fruit since 95% of the participants cultivate it. Forest gardens were found to the main source of their food and livelihood security whereby 44% of the indigenous communities rely on forest garden for income. The forest gardens provide various harvests whereby 63% were inherited from their families The forest gardens also supported agrobiodiversity due to the mixed cropping approach of the participants. The forest garden practices are preserved by local and traditional knowledge of the indigenous communities as it is passed down verbally and practically through generations. The culture and social values of the indigenous communities are impacted by the practices of the forest gardens via taboo and rules. Ultimately, these practices make the forest gardens a unique landscape. Main challenges of the preservation of forest gardens were discovered to be the abandonment of forest gardens due to younger generations not taking over the forest gardens which also led to a loss of the traditional agricultural knowledge. Moreover, the forest gardens constantly faced developmental encroachment due to land ownership issues whereby the indigenous communities do not have grants on the forest garden lands. This led to the destruction of forest gardens by organizations that bought the land. There is a need for strong collaboration between indigenous communities and governmental agencies for the sustainability of forest gardens. Moreover, awareness on the harvests and benefits of forest gardens are vital for not just the indigenous communities but also the public via media exposure to conserve the forest gardens.